EFFECTIVENESS OF CREDIT UTILIZATION AMONG FARMERS IN UGHELLI NORTH LOCAL GOVERNMENT AREA OF DELTA STATE, NIGERIA - Ikpoza, E. A.; Ohwo, O. A.; Nwajei, C. A.; Tabuanu, C. O. (Journal of Agripreneurship and Sustainable Development, 2020)
The study sought to examine the effectiveness of credit utilization among farmers in Ughelli North Local Government Area of Delta State, Nigeria. Multi-stage random sampling technique was used in selecting 120 farmers from 20 villages randomly selected from the 5 (five) clans. Descriptive and inferential statistics was used to analyze the data. The result revealed that the respondents were predominantly males and married (56.7%). Majority (50%) had only six (6) years of formal education and 51.7% of them had between 0.50 - l.5 ha of farm size. Many of (61.2 %) also did not belong to any form of farmer association and 67.8% had other sources of income to support their farm income. Nigerian Agricultural Cooperation and Rural Development Bank (NACRDB) had the greatest mean response of 3.83 as a source of credit to farmers in the study area. The farmers had very few (20%) contacts with extension agents. The probit regression result indicated that, membership in farmers’ association, number of visit by extension agents and farming experience were statistically significant at P≤0.05 confidence level. The chi-square value of 14.64 with a p-value less than 0.046 implies that the independent variables were statistically significantly in predicting the log likelihood of effective use of micro credit by respondents. It was concluded that there was no effectiveness in the utilization of credit by farmers in the study area. The study recommended prompt processing of loan applications and timely disbursement of loans to successful applicant; proper monitoring of credit utilization by credit agents; increasing amount of loans to farmers as this will help to increase their size and operation and ensure food security and Government intervention to reduce the high rate of lending by micro credit institutions.